Accuracy of liver stiffness, spleen stiffness, and LS‐spleen diameter to platelet ratio score in detection of esophageal varices: Systemic review and meta‐analysis. Issue 10 (30th May 2018) - Manatsathit, Wuttiporn; Samant, Hrishikesh; Kapur, Saurabh; Ingviya, Thammasin; Esmadi, Mohammad; Wijarnpreecha, Karn; McCashland, Timothy
Abstract: Background and Aim: There is increasing evidence of non‐invasive measurement using elastography such liver stiffness (LS), spleen stiffness (SS), and LS‐spleen diameter to platelet ratio score (LSPS) for detection of esophageal varices (EV); however, data regarding comparison between these three parameters are limited. Methods: We performed a systemic review and meta‐analysis of studies evaluating performance of LS, SS, and LSPS for detection of EV and high risk/clinically significant EV (HREV). Pooled sensitivity, specificity, log diagnostic odd ratio (LDOR), and area under the receiver operating characteristic curve (AUC) of LS, SS, and LSPS for detection of EV and HREV were analyzed and compared. Publication bias was assessed by Deeks' funnel plot. Results: SS and LSPS were superior to LS for detection of EV with higher sensitivity (0.90 and 0.91 vs 0.85), specificity (0.73 and 0.76 vs 0.64), LDOR (3.24 and 3.35 vs 2.26), and AUC (0.899 and 0.851 vs 0.817). For HREV, SS had the highest sensitivity (0.87) followed by LS (0.85) and LSPS (0.82); however, SS had the lowest specificity (0.52), LDOR (2.09), and AUC (0.807) whereas LSPS had the highest specificity (0.77), LDOR (2.74), and AUC (0.861). Conclusion: For detection of EV, we prefer using LSPS and SS over LS when available, while LS, SS, and LSPS cannot be recommended for detection of HREV due to their moderate sensitivity and specificity.